Casting a light on the shoreline: The influence of light pollution on intertidal settings - Lynn, K. Devon; Quijón, Pedro A. (Frontiers in Ecology and Evolution, 2022)
Light pollution is becoming prevalent among other coastal stressors, particularly along intertidal habitats, arguably the most exposed to anthropogenic light sources. As the number of light pollution studies on sandy beaches, rocky shores and other intertidal habitats raises, commonalities, research gaps and venues can be identified. Hence, the influence of light pollution on the behavior and ecology of a variety of intertidal macro-invertebrates and vertebrates are outlined by examining 54 published studies. To date, a large majority of the reported effects of light pollution are negative, as expected from the analysis of many species with circadian rhythms or nocturnal habits, although the severity of those effects ranges widely. Experimental approaches are well represented throughout but methodological limitations in measurement units and standardization continue to limit the proposal of general conclusions across species and habitats. In addition, studies targeting community variables and the explicit influence of skyglow are heavily underrepresented. Likewise, studies addressing the interaction between light pollution and other natural and anthropogenic stressors are critically needed and represent a key venue of research. The nature of those interactions (synergistic, additive, antagonistic) will likely dictate the impact and management of light pollution in the decades ahead.